Analisis Mekanisme Prosedur Kerja Berbagai Sistem Navigasi Satelit di Dunia - Delon Sitompul; Fatimah Azzahra; Derita Ramai Durubanua; Muhammad Alfi Harahap; Ryan Pramana; Muhammad Arif; Elsa Kardian (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study examines the working mechanisms of various global satellite navigation systems, such as GPS, GLONASS, Galileo, and BeiDou, as well as their integration potential across multiple sectors. The research uses a qualitative descriptive approach through literature review of relevant scientific sources. All satellite navigation systems operate based on the principle of triangulation using radio signals from satellites equipped with high-precision atomic clocks. The procedure includes satellite deployment, signal transmission, distance measurement, and position calculation by receiver devices.The results show that although each system has distinct technical characteristics and strategic orientations, integration between systems—through GNSS, SBAS, radar, and Earth observation technologies—can enhance the accuracy, reliability, and coverage of global navigation services. These systems offer wide-ranging benefits in areas such as transportation navigation, fleet tracking, disaster mitigation, environmental conservation, and military applications. This research emphasizes the importance of understanding the procedures and integration of satellite navigation systems to support cross-sector operational efficiency and strengthen technological resilience in the face of global challenges.